Preliminary Results From Probe of the Moon's Dust Environment. Issue 14 (8th April 2014) - Kumar, Mohi
<x xml:space="preserve">Abstract</x> NASA's Lunar Atmosphere and Dust Environment Explorer (LADEE), a robotic mission with the primary goal of gathering detailed information about the composition and structure of the thin lunar atmosphere, was launched on 6 September 2013. Since the spacecraft reached the Moon on 6 October, LADEE has returned streams of data important to understanding how dust is distributed above the lunar surface; where sources and sinks of lunar atmospheric dust can be found; and how dust distribution, sources, and sinks change through time.